AN ANALYSIS OF FLOUTING MAXIM IN ANIMATED MOVIE THE EMPEROR’S NEW GROOVE: A PRAGMATIC APPROCH - Sitinjak, Lasmaida; Saragi, Christina Natalina; Manurung, Lastri Wahyuni (Universitas Hamzanwadi, 2024)
This research discusses a pragmatic study, focusing on the film